Equations 2022
DOI: 10.37394/232021.2022.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Taylor and Maclaurin Series Representations of the Nield-Kuznetsov Function of the First Kind

Abstract: Taylor and Maclaurin series and polynomial approximations of the Standard Nield-Kuznetsov function of the first kind are obtained in this work. Convergence and error criteria are developed. The obtained series represent alternatives to the existing asymptotic and ascending series approximations of this integral function, and are expected to provide an efficient method of computation that is valid for all values of the argument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In a recent article, Alderson and Hamdan, [1], investigated Taylor and Maclaurin series and polynomial representations of the standard Nield-Kuznetsov function of the first kind, 𝑁𝑖(π‘₯). This function arises in the solution to Airy's inhomogeneous ordinary differential equation, [2], of the form…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent article, Alderson and Hamdan, [1], investigated Taylor and Maclaurin series and polynomial representations of the standard Nield-Kuznetsov function of the first kind, 𝑁𝑖(π‘₯). This function arises in the solution to Airy's inhomogeneous ordinary differential equation, [2], of the form…”
Section: Introductionmentioning
confidence: 99%
“…where 𝑅 ∈ β„œ. Hamdan and Kamel, [3], showed that the general solution to (1) is expressible in the form:…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations